Assessment of the Efficacy and Safety of a New Treatment for Head Lice. (30th October 2012) - Mac-Mary, Sophie; Messikh, Rafat; Jeudy, Adeline; Lihoreau, Thomas; Sainthillier, Jean-Marie; Gabard, Bernard; Schneider, Catherine; Auderset, Philippe; Humbert, Philippe
Abstract : Infestation with head lice is a widespread, persistent, and recurring issue leading to serious health problems if untreated. We are facing resistance phenomena to usual pediculicides and questions about their direct or cumulative toxicity. The aim of this trial was to assess the efficacy of a new product, free of chemical insecticides but with a physical effect. This product contains components whose antilice efficacy has already been demonstrated, as well as Andiroba oil which asphyxiates the lice and Quassia vinegar which dissolves the chitin of the nits (they are then inactivated). 30 patients with head lice infestation, aged 3–39 years, applied the treatment one to three times, 5 days apart. Cure was defined as the absence of live lice after 5, 10, or 14 days, and symptoms are usually associated with infestation. Easiness and safety of the treatment were assessed by the patients and/or their parents. Overall cure rates were 20% on D5 after one treatment, 37% on D10 after two treatments, and 90% on D14 after three treatments. Symptoms such as itch, scalp dryness, redness, and flakiness rapidly diminished. This treatment seems to be a beneficial addition or a valuable alternative to existing treatments, considering the total absence of chemical insecticides, the absence of drug-resistance induction in head lice, the absence of major toxicological risks compared with usual pediculicides, and the favourable patient use instructions.